Development Of Hybrid Renewable Energy Based Electrical Power Generation System - Raveen Kumar A/L Ramalingam, Raveen Kumar (Universiti Teknologi Petronas, 2010)
Due to the global warming and other effects on Earth, the world is moving towards utilizing renewable energy. Malaysia is situated near to the equator where the ambient temperature remains uniformly high throughout the year, between 27 and 33°C, with an average daily solar radiation of 4500 kWh per square meter and an average daily sunshine duration of about 6-7 hours. Most locations have a relative humidity of 80- 88%, rising to nearly 90% in the highland areas.